Service utilisation and costs of language impairment in children: The early language in Victoria Australian population-based study. (4th July 2017) - Le, HA N. D.; Gold, Lisa; Mensah, Fiona; Eadie, Patricia; Bavin, Edith L.; Bretherton, Lesley; Reilly, Sheena
Abstract: Purpose: To examine (1) the patterns of service use and costs associated with language impairment in a community cohort of children from ages 4–9 years and (2) the relationship between language impairment and health service utilisation. Method: Participants were children and caregivers of six local government areas in Melbourne participating in the community-based Early Language in Victoria Study (ELVS). Health service use was reported by parents. Costs were valued in Australian dollars in 2014, from the government and family perspectives. Depending on age, the Australian adapted Clinical Evaluation of Language Fundamentals – Pre-school, 2nd Edition (CELF-P2) or the CELF, 4th Edition (CELF4) was used to assess expressive and receptive language. Result: At 5, 7 and 9 years respectively 21%, 11% and 8% of families reported using services for speech and/or language concerns. The annual costs associated with using services averaged A612 (A255 to government, A357 to family) at 5 years and A992 (A317 to government, A675 to family) at 7 years. Children with persistent language impairment had significantly higher service costs than those with typical language. Conclusion: Language impairment in 4–9-year-old children is associated with higher use of services and costs to both families and government compared to typical language.